2012
DOI: 10.1007/s12288-012-0172-9
|View full text |Cite
|
Sign up to set email alerts
|

Essential Thrombocythaemia: A Single Institution Experience of 16 Years

Abstract: This presentation is a clinical narrative and long term follow up (6-16 years) of 21 prospectively studied patients with essential thrombocythaemia (ET) in Kuwait. The median age (55.9 years) is younger than reported by others. Two patients were below the age of 40 years with one of them presenting as post-polycytheamia ET at 16 years of age. Twelve patients (57.1 %) remained asymptomatic throughout the period of follow up. Four patients complained of erythromelalgia, three (19 %) suffered from thrombotic epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…JAK2 V617F positivity in ET has been observed from various racial backgrounds ranging from 25% to 70% (Sazawal et al, 2010;Alshemmari et al, 2014). When compared with earlier reports, our results are intermediate with regional studies reported from India; ranging 38% to as high as 70% for JAK2V617F mutational expression (Sazawal et al, 2010;Varghese et al, 2013). (Hamidah et al, 2012;Alshemmari et al, 2014).…”
Section: Discussioncontrasting
confidence: 57%
“…JAK2 V617F positivity in ET has been observed from various racial backgrounds ranging from 25% to 70% (Sazawal et al, 2010;Alshemmari et al, 2014). When compared with earlier reports, our results are intermediate with regional studies reported from India; ranging 38% to as high as 70% for JAK2V617F mutational expression (Sazawal et al, 2010;Varghese et al, 2013). (Hamidah et al, 2012;Alshemmari et al, 2014).…”
Section: Discussioncontrasting
confidence: 57%
“…DOI:http://dx.doi.org/10.7314/APJCP.2015.16.17.7659 Clinico-Hematological Profile in Essential Thrombocythemia: Experience from Pakistan. Most of our patients were asymptomatic (61.9%) and diagnosed inadvertently. This is more or less similar to studies reported from Kuwait (57.1%) and Thailand (54.2%) (Varghese et al, 2013;Duangnapasatit et al, 2015). Nevertheless, symptomatic cases were found to be 38.1% in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The most common symptoms in our patients were weakness (19%); painful burning sensationerythromelalgia (14.2%) and transit limbs ischemia (9.5%). Varghese had reported 19 % of patients presented with erythromelalgia, while 14.1 % had thrombotic episodes and 4.5 % developed bleeding (Varghese et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is different from the study of Kuwait and Thailand where 57.1% and 54.2% of the patient were asymptomatic respectively. [11][12][13] Despite this, 11.76% of the cases in our study were asymptomatic. According to a study, 19% of the patients suffered erythromelalgia, 14.1% had thrombotic events, and 4.5% had bleeding.…”
Section: Discussionmentioning
confidence: 57%
“…According to a study, 19% of the patients suffered erythromelalgia, 14.1% had thrombotic events, and 4.5% had bleeding. 13 The most likely reason for the low number of asymptomatic patients is that they only come to the clinic when they acquire symptoms in our settings. Splenomegaly has been documented in 25% to 50% of ET patients.…”
Section: Discussionmentioning
confidence: 99%